Mental Health Utilization Among Diverse Parenting Young Couples. Issue 1 (11th July 2015) - Albritton, Tashuna; Angley, Meghan; Gibson, Crystal; Sipsma, Heather; Kershaw, Trace
Abstract: Mental health issues often become apparent as adolescents emerge into young adulthood. The use of mental health services is low among adolescents and young adults, and use is particularly low among minorities. In this study, we examine mental health utilization among diverse young parenting couples. The sample consisted of 296 couples. We used the social–personal framework to examine personal, family, partner relationship, and environmental predictors for using mental health services. We used the Actor–Partner Interdependence Model to assess actor and partner effects on mental health utilization. We also examined moderator effects for gender and internalizing and externalizing behaviors. We found that being female, being White, higher income, more conduct problems, and less anxious romantic attachment predicted mental health utilization. Significant moderator effects included depression × gender, depression × medical insurance, and stress × Latino. Implications for community mental health practice include conducting mental health assessments during medical visits and systematic mental health follow‐up for individuals and couples with identified mental health and support needs. Future research should include married couples and the spouse's influence on mental health use and examine relevant parenting factors that may also predict mental health utilization among couples.